The thermoluminescence response of Ge-doped optical fibre subjected to photon irradiation - Abdulla, Y.A.; Amin, Y.M.; Bradley, D.A. (Elsevier, 2001)
A radiation dosimeter based on Ge-doped silica fibre is described. Parameters concerning thermoluminescence (TL) induced by 60Co irradiation are investigated, including activation energies, frequency factors, and reproducibility with dose and fading. It is concluded that Ge-doped silica fibres provide a good basis for medical radiation dosimetry at therapy levels. In particular, doses are reproducible to within 3%, the fibres are reusable and show linearity of dose versus TL output over the approximate range of dose 1 Gy to in excess of 100 Gy. At room temperatures, fading within the first 30 d following irradiation has been found to be of the order of 7%.